2009
DOI: 10.1038/onc.2009.311
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock cognate 70 protein secretion as a new growth arrest signal for cancer cells

Abstract: Earlier studies indicated that density-arrested cancer cells released an unidentified growth inhibitor whose secretion was prevented by overexpression of the lysosomal protease cathepsin D (cath D). In this study, this growth inhibitor was purified by affinity chromatography and identified as the heat shock cognate 70 protein (hsc70) based on its peptide microsequencing and specific antibody recognition. Among intracellular proteins, including other heat shock proteins, only constitutive hsc70 was secreted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 53 publications
0
37
0
1
Order By: Relevance
“…Despite its similarity across many taxa, Hsc70 is diverse in its functions (Takei & Haucke, 2001;Zhao et al, 2009). In the mosquito Aedes aegypti, Hsc70 isoform B is differentially expressed in response to treatment with heat shock (Nirdé et al, 2010); however, it was identified in an immune response-activated haemocyte library derived from the mosquito Armigeres subalbatus (Bartholomay et al, 2004). The increased expression of Hsc70 has also been shown in Anopheles gambiae when infected by the o'nyong-nyong virus (ONNV) (Sim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its similarity across many taxa, Hsc70 is diverse in its functions (Takei & Haucke, 2001;Zhao et al, 2009). In the mosquito Aedes aegypti, Hsc70 isoform B is differentially expressed in response to treatment with heat shock (Nirdé et al, 2010); however, it was identified in an immune response-activated haemocyte library derived from the mosquito Armigeres subalbatus (Bartholomay et al, 2004). The increased expression of Hsc70 has also been shown in Anopheles gambiae when infected by the o'nyong-nyong virus (ONNV) (Sim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…147,148 It is worth mentioning that besides its intracellular location, HSPA8 is also detected in the extracellular space. It may derive from dying cells, but can also be actively released from intact cells, either free [149][150][151] or associated with exosomes. 152 Extracellular HSPA8 inhibits tumor cell growth 151 and modifies cell viability.…”
Section: Hspa8 Functionsmentioning
confidence: 99%
“…It may derive from dying cells, but can also be actively released from intact cells, either free [149][150][151] or associated with exosomes. 152 Extracellular HSPA8 inhibits tumor cell growth 151 and modifies cell viability. This property still remains a matter of debate since both proapoptotic and anti-apoptotic effects are observed.…”
Section: Hspa8 Functionsmentioning
confidence: 99%
“…Subsequent studies of these cells revealed that this overexpression prevented the release of HSC70, which led to the malignant phenotype [229]. immunosurveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it can catalyze the disassembly of clathrin cages [227] and has been implicated in the regulation of tumorigenesis and apoptosis [228]. With the assistance of co-chaperones, HSC70 can be recruited to the intracellular membrane [227], but can be released from cells as a result of active secretion [229]. Humoral autoimmune reactions against HSC70 have been documented in patients with cancer-associated retinopathy (characterized by visual loss and impairment) an ocular manifestation of underlying cancer, generally small-cell lung carcinoma [230].…”
Section: Discussionmentioning
confidence: 99%